Bibliometric Analysis of Omnichannel Retailing Trends : Insights from the Last 19 Years - Rastogi, Ruchika; Saha, Shantanu (Indian Journal of Marketing, 2025)
Purpose : This study investigated the evolution of scholarly research on omnichannel retailing, an area that still lacked a comprehensive bibliometric assessment. By synthesizing existing literature, the study aimed to highlight key research trends, influential works, and thematic developments in the field. Design/Methodology/Approach : A bibliometric analysis was conducted on 279 publications indexed in the Scopus database from 2002 to 2021. VoSviewer software was used to create a visual map of recurring research terms. The study identified key articles, authors, and journals, while a content analysis of highly cited papers and recent works further refined the understanding of omnichannel retailing. Findings : The results revealed the most influential contributions to the field, categorized into five major research clusters. The analysis highlighted key authors, sources, and documents that shaped omni-channel retailing literature. Content analysis further captured evolving research priorities and emerging themes from recent publications. Practical Implications : The study consolidated fragmented literature, offering insights for researchers, practitioners, and retailers. Understanding dominant themes and research trajectories helped businesses implement effective omnichannel strategies while guiding future academic investigations. Originality : This study uniquely combined bibliometric and content analysis to systematically map omni-channel retailing research. By providing a structured overview of existing studies, it enhanced theoretical comprehension and practical application of omnichannel strategies.